Before We Were Us - Hunter, Denise, 1968- (Thorndike, Maine : Center Point Large Print, 2024)
"She cant remember. He cant forget. When Lauren Wentworth wakes up in the hospital after falling from a ladder, she has more questions than answers. Way more. She knows where she is -- the wilds of New Hampshire. But shes apparently lost the last four months of her life. Is she really contemplating forfeiting her big-city dream job for a position at a rustic resort? And how did her number one nemesis become her adoring boyfriend? Jonah Landry is crushed to learn Lauren has forgotten their entire summer together. Terrified of losing her for good, he determines to help her remember their deep connection as she finishes her obligation to the resort. But soon it becomes apparent Lauren doesnt want to remember falling in love with him or rethinking the entire course of her career. She wants to pretend the summer never happened and move on with her life. Without him. As Lauren falls back into the steady routines of resort work with Jonah, shes relieved her memories havent returned and remains resolute about her big-city future. But as autumn leads into winter, she begins to see glimpses of the Jonah shes forgotten. Will she be able to resist the steady love of this patient man? Or is her heart destined for its own freefall?"--
Keywords: Amnesiacs -- Fiction; Man-woman relationships -- Fiction; Summer resorts -- New Hampshire; Fiction; Resorts -- Employees; Fiction; Country life -- Fiction; New Hampshire -- Fiction; Romance fiction; Christian fiction; Large print books